Effect of Yin-Xing-Tong-Zhi Tablets on Improving Vascular Cognitive Impairment No Dementia. (26th April 2018) - Pan, Weidong; Zhu, Wei; Gao, Qi; Liao, Weilong; Gao, Penglin; Liu, Te
Abstract : Objective . Observe the effect of the Chinese herbal extracts, Yin-Xing-Tong-Zhi, in tablet form, on improving vascular cognitive impairment no dementia (VCIND). Methods . Sixty-eight patients with VCIND were divided randomly into treatment and placebo groups with oral administration of Yin-Xing-Tong-Zhi tablets (YXTZTs) or placebo, respectively, for 24 weeks. Alzheimer's Disease Assessment Scale-Cognitive (ADAS-Cog) subscale score, MMSE score, Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-Plus) score, expression of interleukin- (IL-) 6, IL-8, and tumor necrosis factor- (TNF-) α in serum, and variation of blood-lipid levels were evaluated at different time points. Results . At weeks 12 and 24, the scores for the ADAS-Cog, CIBIC-Plus, and MMSE of the treatment group were significantly lower than those of the control group (P < 0.05 ). All clinical scales at week 24 of the control group were significantly different from those before treatment (P < 0.05 ). Expression of IL-6, IL-8, and TNF- α in the two groups was reduced significantly with variation of the clinical scales of cognitive impairment. Conclusion . YXTZTs may delay the development of cognitive impairment in VCIND patients by modulating expression of VCIND-associated proinflammatory factors.